PEMBEBANAN HIPOTEK ATAS KAPAL LAUT MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN (STUDI KASUS DI PT. X TAHUN 2020) - Alifia Nashira; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2020)
Shipping companies in the era of globalization are growing rapidly which causes shipping activities to also develop. This development makes the shipping sector require large capital to run its business. Ships as facilities and infrastructure for marine transportation and as objects that have economic value that can be used as collateral. To get a large capital requires assistance in the form of credit which is used to buy ships and can be used as collateral by charging a mortgage on the ship. Ship collateral is one of the material rights as collateral for debt repayment. In order for a ship to be subject to a mortgage, it must be registered at an Indonesian port and must be done with an authentic deed. The issue that will be discussed is regarding the process of loading a marine mortgage in accordance with law number 17 of 2008 concerning shipping and the consequences of this guarantee. The result of this research is that ships that are charged a mortgage will be issued a mortgage grosse deed. The grosse mortgage deed has the same executorial power as the court verdict which has permanent legal force. As a result of this guarantee, default may occur because the debtor does not fulfill the agreed performance. The occurrence of default is the same as bad credit that causes the ship to be towed. Then the ship will be executed with the creditors and through the auction agency.